Comparison of Differential Grounding Electrode with Earth Resistance - Uthitsunthorn, Dusit; Vimuttisoongviriya, Cheellawad (Srinakharinwirot University Engineering Journal, 2025)
This research investigates and compares variations in grounding electrode characteristics affecting soil resistance values, utilizing geological data from Buriram Province. The study area is characterized by plateaus and volcanic terrain. Three distinct areas with varying soil conditions are consists: Prakhon Chai District, Mueang Buriram District, and Khu Mueang District, were selected for experimentation to ascertain soil resistance values correlated with geological features. The study involved measuring the resistance of rods and plates of different dimensions. Results indicate that employing a copper bar ground stake with a diameter of 14.20 millimeters and a length of 240 centimeters yielded the lowest soil resistance values in Prakhon Chai District is 6.43 ohms, followed by Mueang Buriram District is 7.18 ohms, and the highest value was observed in Khu Mueang District is 353 ohms. Similarly, burying a copper sheet is 30x30 square centimeters to a depth of 150 centimeters revealed varying soil resistivity values: Prakhon Chai District is 10.3 ohms, Mueang Buriram District is 12.5 ohms, and Khu Mueang District is 368 ohms. Soil classification tests identified sandy clay soil with high soil moisture content in Prakhon Chai District and Mueang Buriram District, resulting in low soil resistance and efficient electric current conduction. Conversely, Khu Mueang District exhibited sandy soil mixed with silt, facilitating easy water permeation and consequently yielding the highest soil resistance value.